Israel’s Policies to the US-Iraq Wars of 1991 and 2003: - Ünal, Derviş Fikret (Indonesia Center for Middle East Studies, 2023)
The United States waged two important wars against Iraq under the rule of Saddam Hussein, which had significant regional and global consequences. Israeli policy and decision-makers, among whom the IDF[i] was strongly influential as well, followed realist policies on these wars based on interest calculations. This article studies and makes an analysis of Israeli policies on both wars. In this vein, the article firstly touches upon the theory of realism to emphasize the role of interest defined in terms of power in foreign policy. Then, this article argues that Israel made rational choices in the US-Iraq Wars of 1991 and 2003. Finally, the article concludes that Israel continues to be guided first and foremost by national security concerns in the implementation of its foreign policy, which corresponds to the thinking of realist theory, as recently seen in the Syrian civil war, which erupted in March 2011. [i] The IDF: Israel Defense Forces, the military of the State of Israel.